Differential neural processing of social exclusion in adolescents with non-suicidal self-injury: An fMRI study. (30th September 2016) - Groschwitz, Rebecca C.; Plener, Paul L.; Groen, Georg; Bonenberger, Martina; Abler, Birgit
Abstract: Non-suicidal self-injury (NSSI) is highly prevalent in adolescence and has been suggested as an autonomous diagnosis in the Diagnostic and Statistical Manual (DSM-5). Social rejection is as potential risk-factor for NSSI and depression in adolescence. Objectives of this study were to identify differences in neural processing of social rejection in depressed adolescents with and without co-morbid NSSI and healthy controls. Participants were 28 depressed adolescents (14 with co-morbid NSSI, 79% females) and 15 healthy controls, with an average age of 15.2 years ( SD =1.8). Social exclusion was implemented using the Cyberball paradigm 'Cyberball' during functional magnetic resonance imaging (fMRI). All participants reported feelings of social exclusion after fMRI scanning. Investigating the effects of NSSI, we found that depressed adolescents with NSSI showed relatively enhanced activation of the medial prefrontal cortex (mPFC) and the ventrolateral prefrontal cortex (vlPFC) compared to depressed adolescents without NSSI and also compared to healthy controls. Results point towards divergent processing of social exclusion in depressed adolescents with NSSI as compared to adolescents with mere depression in brain regions previously related to the processing of social exclusion. This finding of distinct neurophysiological responses may stimulate further research on individual treatment approaches. Highlights: Differential neural processing of social exclusion in adolescents with NSSI. Adolescents with NSSI differ significantly from adolescents with depression. Adolescents with NSSI differ significantly from healthy controls.